ANALISIS MODEL SAM/R PADA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN MOTIVASI BELAJAR SISWA - Aqidatul Izza; Evi Fatimatur Rusydiyah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2020)
This study discusses the analysis of the SAM / R model on Islamic religious education teachers in developing learning motivation. The purpose of this study was to determine the role of Islamic Religious Education teachers to develop student learning motivation and the application of the SAM/ R model to Islamic Religious Education teachers in developing student motivation, and the impact of the SAM/R model on student motivation in MTsN 1 Sidoarjo. This research uses descriptive research method with qualitative approach. Data collection uses observation, questionnaire, interview and documentation. The SAM/R model is a way to shift the teaching and learning process to become more meaningful and highly innovative, through various levels in technology integration. The results of the study show that: 1) The teacher really understands its role, this is evidenced that the PAI teacher does a variety of ways and efforts to develop student motivation. Although PAI teachers do it in different ways, they have the same goal; 2) The teacher applies the SAM / R model according to the stages. From the lowest to the highest level, namely from the level of Substitution, Augmentation, Modification, to Redefinition; 3) Students are motivated, this is evidenced by the enthusiasm of students in learning that has increased.